Pengaruh Transaksi Pihak Berelasi atas Hubungan Profitabilitas, Kebijakan Hutang, dan Preferensi Risiko Eksekutif terhadap Tax Avoidance: Studi Pada Perusahaan Sektor Energi Yang Terdaftar Di BEI Periode 2019-2021 - Ni Kadek, Budastri Sapta Reni; Yasa, I Nyoman Putra (Universitas Pendidikan Ganesha, 2023)
The purpose of this research is to examine the influence of profitability, debt policy and executive risk preferences on tax avoidance, as well as to examine the effect of Related Party Transactions in moderating the influence between profitability, debt policy and executive risk preferences. This research is a quantitative study using secondary data obtained from the financial reports of companies listed on the Indonesia Stock Exchange. The population in this study are energy sector companies listed on the Indonesia Stock Exchange in the 2019-2021 period, namely 81 companies. The method of determining the sample used was purposive sampling obtained by 22 companies as a sample. Data analysis technique used is descriptive data analysis technique, regression test, and test the coefficient of determination and moderation regression test. The results of this study indicate that Profitability has a significant negative effect on tax avoidance, and debt policy and executive risk preferences have a significant positive effect on tax avoidance, Related Party Transactions are able to strengthen the relationship between profitability, debt policy and executive risk preferences on tax avoidance.